Japanese University Internationalization Strategies: An International Exchange Program Case Study - Firkola, Peter (Archives of Business Research, 2022)
This paper examines a short-term exchange program at a leading Japanese university. This program is a main component of the university's internationalization strategy. The core components of the program, as well as the organizational structure, are first introduced. The challenges, as well as the achievements of the program, are then examined. Finally, the program is discussed in the context of the overall university internationalization process.